Predictors of receiving a diagnosis, referral and treatment of depression in people on antiretroviral therapy in South African primary care: a secondary analysis of data from a randomised trial. Issue 12 (14th October 2020) - Zani, B.; Fairall, L.; Petersen, I.; Folb, N.; Bhana, A.; Thornicroft, G.; Hanass‐Hancock, J.; Lund, C.; Bachmann, M.; ,
Abstract: Objective: To describe the receipt of a diagnosis, referral and treatment for depression in people receiving antiretroviral therapy (ART), with depressive symptoms and attending primary care clinics in South Africa, and investigate factors associated with receiving these components of care. Methods: This is a secondary analysis of data from a randomised controlled trial of an intervention intended to improve detection and treatment of depression in primary care patients receiving ART. In this analysis, we combined cross‐sectional and longitudinal data from the intervention and control arms. Using regression models and adjusting for intra‐cluster correlation of outcomes, we investigated associations between socioeconomic characteristics, depressive symptoms, stress, disability and stigma, and receipt of a diagnosis, referral and treatment for depression. Results: Of 2002 participants enrolled, 18% reported a previous diagnosis of depression by a healthcare worker and 10% reported having received counselling from a specialist mental health worker. Diagnosis, referral and counselling during the follow‐up period were appropriately targeted, being independently more frequent in participants with higher enrolment scores for depressive symptoms, stress or disability. Participants with higher stigma scores at enrolment were independently less likely to receive counselling. Severe socio‐economic deprivation was common but was not associated with treatment. Conclusion: While the receipt of a diagnosis, referral and treatment for depression were uncommon, they seemed to be appropriately targeted. Socio‐economic deprivation was not associated with treatment. Abstract : Objectif: Décrire la réception d'un diagnostic, de l'orientation et du traitement pour la dépression chez les personnes recevant un traitement antirétroviral (ART), présentant des symptômes dépressifs et fréquentant des cliniques de soins primaires en Afrique du Sud, et étudier les facteurs associés à la réception de ces éléments de soins. Méthodes: Il s'agit ici d'une analyse secondaire des données d'un essai contrôlé randomisé d'une intervention destinée à améliorer la détection et le traitement de la dépression chez les patients sous ART dans les soins primaires. Dans cette analyse, nous avons combiné les données transversales et longitudinales des bras d'intervention et témoin. En utilisant des modèles de régression et en ajustant la corrélation intra‐grappes des résultats, nous avons étudié les associations entre les caractéristiques sociodémographiques, les symptômes dépressifs, le stress, l'invalidité et la stigmatisation, et la réception d'un diagnostic, d'une orientation et d'un traitement pour la dépression. Résultats: Sur 2.002 participants inscrits, 18% ont déclaré un diagnostic antérieur de dépression par un agent de santé et 10% ont déclaré avoir reçu des conseils d'un agent spécialisé pour la santé mentale. Le diagnostic, l'orientation et le conseil pendant la période de suivi ont été ciblés de manière appropriée, étant indépendamment plus fréquents chez les participants ayant des scores d'inscription plus élevés pour les symptômes dépressifs, le stress ou l'invalidité. Les participants ayant des scores de stigmatisation plus élevés à l'inscription étaient indépendamment moins susceptibles de recevoir des conseils. La privation socioéconomique sévère était courante mais n'était pas associée au traitement. Conclusion: Bien que la réception d'un diagnostic, l'orientation et le traitement de la dépression soient rares, ils semblaient bien ciblés. La privation socioéconomique n'était pas associée au traitement.